Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) for Hemorrhagic Shock. (5th September 2018) - Cannon, Jeremy; Morrison, Jonathan; Lauer, Cynthia; Grabo, Daniel; Polk, Travis; Blackbourne, Lorne; Dubose, Joseph; Rasmussen, Todd
Abstract: This clinical practice guideline (CPG) reviews the range of accepted management approaches to profound shock and post-traumatic cardiac arrest and establishes indications for considering Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) as a hemorrhage control adjunct. The specific management approach – within the parameters of mission, resources, and tactical situation – will depend on the casualty's physical location, mechanism and pattern of injury, and the experience level of the surgeon. The optimal management strategy is best determined by the surgeon at the bedside.